Create Fair Value in Related Parties - Kavaldjieva, Kalina (Research Papers, 2023)
The main goal of all governing bodies is to make correct management decisions, which are legal and show efficient and good management of enterprises. In the case of transactions between related parties, it is necessary to derive their fair value.The purpose of the research in the present study is to determine the influence of different methods for deriving fair value.The research thesis is that improving the understanding of the application of the various valuation methods would lead to a more correct and reliable determination of the fair value in the presence of related parties, which in turn would lead to more justified and more adequate management decisions.
Keywords: Profit; Evaluation; Fair value; Related parties; Market price; Risk